Improvement of Long COVID symptoms over one year - Oliveira, Carlos R.; Jason, Leonard A.; Unutmaz, Derya; Bateman, Lucinda; Vernon, Suzanne D. (Frontiers in Medicine, 2023)
Importance: Early and accurate diagnosis and treatment of Long COVID, clinically known as post-acute sequelae of COVID-19 (PASC), may mitigate progression to chronic diseases such as myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Our objective was to determine the utility of the DePaul Symptom Questionnaire (DSQ) to assess the frequency and severity of common symptoms of ME/CFS, to diagnose and monitor symptoms in patients with PASC. Methods: This prospective, observational cohort study enrolled 185 people that included 34 patients with PASC that had positive COVID-19 test and persistent symptoms of >3 months and 151 patients diagnosed with ME/CFS. PASC patients were followed over one year and responded to the DSQ at baseline and 12 months. ME/CFS patients responded to the DSQ at baseline and one year later. Changes in symptoms over time were analyzed using a fixed-effects model to compute difference-in-differences estimates between baseline and 1-year follow-up assessments. Participants: Patients were defined with PASC if they had a previous positive COVID-19 test, were experiencing fatigue, post-exertional malaise, or other unwellness for at least 3 months, were not hospitalized for COVID-19, had no documented major medical or psychiatric diseases prior to COVID-19, and had no other active and untreated disease processes that could explain their symptoms. PASC patients were recruited in 2021 and ME/CFS patients were recruited in 2017. Results: At baseline, patients with PASC had similar symptom severity and frequency as patients with ME/CFS and satisfied ME/CFS diagnostic criteria. ME/CFS patients experienced significantly more severe unrefreshing sleep and flu-like symptoms. Five symptoms improved significantly over the course of one year for PASC patients including fatigue, post-exertional malaise, brain fog, irritable bowel symptoms and feeling unsteady. In contrast, there were no significant symptom improvements for ME/CFS patients. Conclusions and Relevance: There were considerable similarities between patients with PASC and ME/CFS at baseline. However, symptoms improved for PASC patients over the course of a year but not for ME/CFS patients. PASC patients with significant symptom improvement no longer met ME/CFS clinical diagnostic criteria. These findings indicate that the DSQ can be used to reliably assess and monitor PASC symptoms.